Ir(NHC)-Catalyzed Synthesis of β-Alkylated Alcohols via Borrowing Hydrogen Strategy: Influence of Bimetallic Structure - Sung, Kihyuk; Lee, Mi hyun; Cheong, Yeon Joo; Kim, Yu Kwon; Yu, Sungju; Jang, Hye Young (Advanced Synthesis and Catalysis, 2021)
Multi N-heterocyclic carbene(NHC)-modified iridium catalysts were employed in the β-alkylation of alcohols; dimerization of primary alcohols (Guerbet reaction), cross-coupling of secondary and primary alcohols, and intramolecular cyclization of alcohols. Mechanistic studies of Guerbet reaction, including kinetic experiments, mass analysis, and density functional theory (DFT) calculation, were employed to explain the fast reaction promoted by bimetallic catalysts, and the dramatic reactivity increase of monometallic catalysts at the late stage of the reaction. (Figure presented.).
Keywords: borrowing hydrogen; Guerbet reaction; iridium; multi-NHC; β-alkylation